“Impact of General Election on Stock Exchange with special reference to BSE and NSE index in INDIA” - et. al., Dr. Girish A Bodhankar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study was carried out by considering the movement of the two major Index of stock markets in India called SENSEX and NIFTY of BSE and NSE stock exchanges. For the analysis of the impact of general election on the stock market, the period was considered as of thirty-day span before and after the election. and checked the volatility of return during the selected period of elections. The data was collected for 3 months before and after the last 5 loksabha election related to NSE & BSE. To make the study fruitful data were considered the last five loksabha elections in India to find out the exact impact and to prove the objective of the paper. The authentic source of the date are the websites of NSE and BSE, RBI, Money control etc. To analyze the impact, used the model in which we analyse the opening values and the closing values of stock markets index during the election period and accordingly the return and the volatility of return is calculated. By doing the study it is noticed that there is significant impact of general election on the performance of stock market and its index.